Pakcoy Plant Sprinklers Based Internet Of Things - Riasti, Savira; Riadi, Aditya Akbar; Chamid, Ahmad Abdul (Jurusan Teknologi Informasi Universitas Semarang, 2021)
Agriculture is a pillar of the economy a nation, with the system and the implementation of good agricultural, so will go the nation economic.One of the causes of the lack of agricultural productivity in Indonesian that is some farmers in Indonesian still relied on climate change rain without blemish. Climate change has caused planting patterns the farmers, so that in the end agricultural products planted could not stable , any process planting .The instability caused the price of agricultural products to be very significant plant at a certain season.This is what causes the thing farmers have to produce more energy and the cost of extra do watering manually so that of the trees can grow fertile and can be harvest pakcoy especially in plants .To overcome the problems hence writers try to make sprinkler system plant with using microcontroller Wemos D1 R1 of experiment to the republic of Indonesian that in arable land plant with using soil moisture capacitive sensors that is going to be the moisture the ground in plants can be monitored over long distances through the android application named Blynk. The system will shut when discharging is out of danger at the boundary moisture expected means of sensors the humidity and turn off water pump.